Land Registration Problems Related to Installation & Maintenance of Land Boundary Signs - Dini Wulansari; Achmad Sulchan; Ngadino Ngadino (Sultan Agung Notary Law Review, 2020)
The implementation of land registration activities itself is a government obligation which aims to provide legal certainty in order to protect the rights of land owners which also functions to determine the status of land parcels, who owns it, types of rights, land area, and use and utilization of the land as mandated by the Law. invite. In this research, the objective of this research is to find out what are the problems in land registration, the causative factors, and the role of BPN in dealing with the problems that occur.The approach method used in this research is the sociological juridical approach. This approach is taken to understand law in the context of its society, namely a non-doctrinal approach.The data needed, namely the types of primary data and types of secondary data, were taken by observation, interview and documentation methods. Methods of data analysis using qualitative descriptive analysis, meaning that this research uses data collection methods obtained directly from sources, either in writing or orally. The results showed that there are still land rights holders who do not fulfill their obligation to put up land boundary signs and the factors that cause land rights holders do not fulfill their obligations are due to lack of legal awareness. The role of BPN itself is to disseminate information to the community to install and maintain land boundary signs for the common interest and for the smoothness of the land registration process.